Age-Associated Deficits in Pattern Separation Functions of the Perirhinal Cortex: A Cross-species Consensus - Burke, S.N. (2011)
Normal aging causes a decline in object recognition. Importantly, lesions of the perirhinal cortex produce similar deficits and also lead to object discrimination impairments when the test objects share common features, suggesting that the perirhinal cortex participates in perceptual discrimination. The current experiments investigated the ability of young and aged animals to distinguish between objects that shared features with tasks with limited mnemonic demands. In the first experiment, young and old rats performed a variant of the spontaneous object recognition task in which there was a minimal delay between the sample and the test phase. When the test objects did not share any features (‘Easy’ perceptual discrimination) both young and aged rats correctly identified the novel object. When the test objects contained overlapping features, however, only the young rats showed an exploratory preference for the novel object. In Experiment 2, young and aged monkeys were tested on an object discrimination task. When the object pairs were dissimilar, both the young and aged monkeys learned to select the rewarded object quickly. In contrast, when LEGOs® were used to create object pairs with overlapping features, the aged monkeys took significantly longer than did the young animals to learn to discriminate between the rewarded and the unrewarded object. Together, these data indicate that behaviors requiring the perirhinal cortex are disrupted in advanced age, and suggest that at least some of these impairments may be explained by changes in high-level perceptual processing in advanced age.